Synthesis of C-BN hybride nano structures - Guler, O.; Evin, E.; Guler, S. H.; Selen, V.; Yardimci, S.; Keles, A. (Natl Inst Optoelectronics, 2015)
This study reports on the mechano-thermal synthesis of carbon boron nitride nano structures from elemental graphite and boron nitride powders. Initially, amorphous hybrid structure was obtained by high energy ball milling technique from hexagonal graphite and hexagonal boron nitride powders. X-ray spectra taken from ball milled samples indicated that the hexagonal graphite and boron nitride, composed of layers, was transformed into the amorphous hybrid for a milling time of 20 h by the way of high energy input. Subsequent isothermal annealing of milled hybrid powders was conducted at 1300 degrees C for 2 h in Ar gas. It was revealed via investigation of transmission electron microscopy that carbon - boron nitride hybrid nano structures were formed after annealing.
Keywords: Nanotubes; Carbon; Boron nitride; Hybrid structure; Ball milling